Bushido dalam Masyarakat Jepang Modern - Wibawarta, Bambang (UI Scholars Hub, 2006)
Bushido is most often translated as the way of the warrior caste in Japan. Bushi refers to warriors in feudal Japan while do means several things including: the correct way, the path, or the road. Another interpretation of Bushido could be the way of preserving peace through the use of force. Bushido comes out of Buddhism, Confucianism, and Shintoism. The combination of these schools of thought and religions has formed the code of warrior values known as Bushido. A key to our understanding of how the concepts of Bushido fit into Japanese modern lives is to understand the historical and societal aspects of Bushido. Today, this meaning can be modernized to include minimizing violent conflict. The code of Bushido, the Samurai's code of honor, upholds loyalty, discipline, total dedication, honor and valor, and numerous examples of these elements can be witnessed today or in recent history.